2022
DOI: 10.1186/s12966-022-01397-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Canadian 24-Hour Movement Guidelines among infants and associations with development: a longitudinal study

Abstract: Background To examine: 1) longitudinal adherence to the Canadian 24-Hour Movement Guidelines in a sample of infants and 2) associations between adherence to the guidelines over time and development. Methods Participants were 250 parent-infant dyads from the Early Movers project in Edmonton, Alberta. At 2, 4, and 6 months of age, physical activity, sedentary behaviour, sleep, and development were measured with a parental questionnaire that included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, in a study involving Canadian infants, the percentages meeting all three guidelines were 12.4%, 18.0%, and 27.6% at 2 months, 4 months, and 6 months of age, respectively [ 29 ]. It is noteworthy that the primary distinction between our study and the previously mentioned studies was the notably higher compliance with the recommendation of zero screen time, which was approximately 83% in our sample, in contrast to the lower percentages reported in Australian infants (27.9% at age 3.6 months) [ 28 ] and Canadian infants (37.2% at age 6 months) [ 29 ]. In this study, infants were found to have a daily screen time exposure ranging from a median of 0.5 to 1 hour around the age of 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study involving Canadian infants, the percentages meeting all three guidelines were 12.4%, 18.0%, and 27.6% at 2 months, 4 months, and 6 months of age, respectively [ 29 ]. It is noteworthy that the primary distinction between our study and the previously mentioned studies was the notably higher compliance with the recommendation of zero screen time, which was approximately 83% in our sample, in contrast to the lower percentages reported in Australian infants (27.9% at age 3.6 months) [ 28 ] and Canadian infants (37.2% at age 6 months) [ 29 ]. In this study, infants were found to have a daily screen time exposure ranging from a median of 0.5 to 1 hour around the age of 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a study involving Australian infants with an average age of 3.6 months, only 4% met all the overall guidelines, which included the addition of meeting infant restraint guidelines [28]. Similarly, in a study involving Canadian infants, the percentages meeting all three guidelines were 12.4%, 18.0%, and 27.6% at 2 months, 4 months, and 6 months of age, respectively [29]. It is noteworthy that the primary distinction between our study and the previously mentioned studies was the notably higher compliance with the recommendation of zero screen time, which was approximately 83% in our sample, in contrast to the lower percentages reported in Australian infants (27.9% at age 3.6 months) [28] and Canadian infants (37.2% at age 6 months) [29].…”
Section: Plos Onementioning
confidence: 99%
“…Movement behaviours, including tummy time, physical activity, sedentary behaviour and sleep, are crucial for healthy development during early childhood [ 13 , 14 ]. A study in Canada showed that each additional time point of tummy time recommendation adherence was associated with five to 11 days earlier acquisition of independent sitting, crawling, and independent standing milestones [ 15 ]. However, compliance with the WHO movement behaviours guidelines remains quite low among children under two years old.…”
Section: Suboptimal Status Of Feeding Practices and Movement Behaviou...mentioning
confidence: 99%
“…However, compliance with the WHO movement behaviours guidelines remains quite low among children under two years old. Only 30% of children met the WHO’s recommendations for tummy time (30% in the UK, 29.7% in Australia) [ 15 , 16 ], and more than half of children complied with guidelines regarding sedentary behaviour and sleep duration (57.8% and 76.2% in the UK, and 56.9% and 58.7% in Australia) [ 15 , 16 ]. As in China, limited data exists on movement behaviour practices among infants and young children.…”
Section: Suboptimal Status Of Feeding Practices and Movement Behaviou...mentioning
confidence: 99%
“…Studies conducted in UK and Australia found that half of parents started tummy time until four weeks after birth and no more than one-third of infants met the recommended 30 minutes of tummy time [ 7 , 8 ]. In addition, younger infants tend to exhibit a lower preference for engaging in tummy time activities, often displaying crying, rolling or squirming [ 9 , 11 ]. However, little is known regarding tummy time practices among infants in China and other Asian countries.…”
mentioning
confidence: 99%